VD_FINDINFO Jug / 2022 / 281 vom 8. Oktober 2021 - VD Tribunal cantonal (2021)
VOIES DE FAIT, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, PEINE PÉCUNIAIRE | 106 CP, 126 CP, 144 al. 1 CP, 34 CP, 42 al. 1 CP, 44 al. 1 CP, 47 CP